Mathematical errors of students who enter to university - Gamboa Araya, Ronny (2019)
Many students, who enter the university, have mathematical errors that are shown during the process of construction of new content, and impact their academic performance in the discipline. Many authors have recognized the importance of the study and analysis of errors, as a means for learning and an input for improvement. This article presents the results obtained by analyzing the errors committed by first-year students in the mathematics diagnostic test at the National University, Costa Rica, in the year 2017. The research is qualitative, explanatory and descriptive. The test had 60 unique selection exercises. The students had to write down in the exam brochure all the procedures performed. A random sample of 100 tests was selected. For each item, a choice of tests was made where the students had performed some procedure and the errors were classified according to their origin: mathematical language, spatial information, incorrect inferences or associations, recovery of a previous scheme, incorrect or accidental calculations, and deficiencies in the construction or absence of prior knowledge. The students, in addition to presenting errors in the mentioned categories, presented errors in mathematical contents such as identification of the priority of operations, use of parentheses, concept of absolute value, operations with polynomials, notable formulas, and factorization, among others. The results show that the students present diverse errors and deficiencies in mathematics; therefore, it is necessary to propose strategies, at the university level, to correct this situation and ensure that students have the necessary bases to successfully face the courses of the discipline.